教育研究と教育行政 : 各国の動向(III 共同研究) - 川野辺, 敏; 小島, 弘道; 木村, 浩; 手塚, 武彦 (Bulletin of the Japan Educational Administration Society, 1988)
Every country has not only accumulated the achievements of its educational research practice, but also has placed importance on bilateral/multilateral cooperation with other countries in educational development. However, it is difficult to leave all the research activities exclusively in the hands of government because varied phases are included in educational researches.-theoretical or practical; short-term or long-term. Here we investigate the cases of Britain, France and the Soviet Union in terms of governmental involvement in educational research activities. In order to see the current situation educational research in Britain, we analyze about 1800 projects on list of NFER(1980-1983), and then clarify the major institutions and areas of research, etc. It is the traditional pattern of formulation of policy and decision making in this country that they first establish advisory committees, which carry out investigation and research on educational issues, and suggest policies based on their studies. It is also one of the features of the British system that the research achievements and suggestions are put to policy-formation as well as practice willingly through both formal and informal channels. In France, there are many on-going educational research activities. National educational research organizations have played the major role in both theoretical and practical research in education. Compared with those in Japan and United States, however, educational research activities at unversities are not organized efficiently. Generally speaking, achivements of educational research are accepted positively. Adminstrators tend to regard those research achievements they can use to satisfy immediate needs as more important. However, without long-term view and fundamental objective approach any research can not be highly evaluated academically. Judging from this viewpoint, educational research activities in French universities and academic societies are not active as those in Japan. On the other hand, many specialized educational research insititutions have accumulated practical studies closely related to classrooms. In the Soviet Union, there are the Soviet Union Education Science Academy, universities, and research institutions. In addition, in the local cities and counties, there are "cabinet" (teacher training centers) with similar function to those of research institutions. The Soviet Union Education Science Academy is involved in scientific studies on fundamental issues on education and engaged in the most crucial matters related to organizing national educational system. They study cases at experimental schools or by prominent teachers are widely presented to others to share. The Central Committee of the Soviet Union Communist Party held in February 1988 adopted a recommendation, on the "Perestroika" on education and suggested that the Soviet Union Education Science Academy should be placed under the control of several ministries instead of under the single Ministry of Education.